MOLECULAR ELECTRON IONIZATION CROSS - SECTION AND λ max IN THE STUDIES OF ACTIVITIES OF ALKALOIDS - SREENIVASULU, M.; MURTHY, V.R. (International Journal of Pharma and Bio Sciences, 2014)
Alkaloids are natural products having an important position in forensic chemistry and medicine due to their pharmacological activities.Not many physical properties of alkaloids have been studied so far excepting UV, IR and NMR studies. This paper deals with the evaluation of Molecular electron ionization cross section (Q) through λmax, a parameter available from UV studies. Electron ionization cross - section was primarily conceived to be of use in radiation chemical data, mass spectrometry and thermodynamic studies. But later attempts to correlate Q with structural and related parameters prompted the authors to derive an explicit expression relating λmax and Q. The application of this method to correlate Q and Chemical activity through λ max is a examined and the results are discussed.